The doctrine of forum non conveniens and the discretionary limitation of jurisdiction of the South African Admiralty Court in terms of section 7(1) of the Admiralty Jurisdiction Regulation Act, 105 of 1983, as amended - Malan, Christopher Cyril Martin (Department of Commercial Law, 2025)
[pg 2 missing] On 1 November 1983 Parliament promulgated The Admiralty Jurisdiction Regulation Act, Act 105 of 1983 (hereinafter referred to as "the Act"), which repealed the Colonial Courts of Admiralty Act 1890 of the United Kingdom insofar as it applied in relation to the Republic of South Africa. The Act revolutionised the law applicable to admiralty proceedings in the Republic of South Africa and answered the need for a codified and modern approach toward admiralty law as applied in South Africa, which had been advocated by maritime concerns and jurists for many years. The Act has been described as one which contained "novel, unusual and at times far-reaching provisions” and that in being enacted it was the intention of the Legislature: "to introduce a remedial measure designed to provide what is nowadays referred to as 'a new dispensation' in respect of maritime claims and their enforcement in South Africa". Many statutory rights and remedies not previously part of the English admiralty law as applied in the Supreme Courts of the Republic of South Africa were introduced by the Act. With the extension in the category of "maritime claims" now available to the claimant came a statutory extension of the Court's powers to adjudicate on matters maritime in -terms of the Act brought by "the wandering litigants" of the maritime community.